2021
DOI: 10.1186/s40623-020-01326-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal characteristics of frictional properties on the subducting Pacific Plate off the east of Tohoku district, Japan estimated from stress drops of small earthquakes

Abstract: The east coast of the Tohoku district, Japan has a high seismicity, including aftershocks of the 2011 M9 Tohoku earthquake. We analyzed 1142 earthquakes with $$4.4 \le M_{W} \le 5.0$$ 4.4 ≤ M W ≤ 5.0 that occurred in 2003 through 2018 and obtained spatio-temporal pattern of stress drop on the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The latter, lower Δ could be associated with a temporary reduction in fault strength within the mainshock rupture zone (e.g., Abercrombie, 2014;Kim et al, 2016;Trugman et al, 2017) and/or highlight fault segments that have not fully healed from the large earthquake ground motion (e.g., Moyer et al, 2018;Shaw et al, 2015). Consistent interpretations by Yamada et al (2021) associated high stress drop values with a gradual weakening of the shear strength due to stress concentration during the coseismic slip of the mainshocks. Following the temporal decrease, the median Δ values then increase in the subsequent months, consistent with fault zone healing and an increase in fault strength (e.g., Goebel et al, 2015;Moyer et al, 2018;Vidale et al, 1994).…”
Section: Spatio-temporal Stress Drop Evolutionmentioning
confidence: 93%
“…The latter, lower Δ could be associated with a temporary reduction in fault strength within the mainshock rupture zone (e.g., Abercrombie, 2014;Kim et al, 2016;Trugman et al, 2017) and/or highlight fault segments that have not fully healed from the large earthquake ground motion (e.g., Moyer et al, 2018;Shaw et al, 2015). Consistent interpretations by Yamada et al (2021) associated high stress drop values with a gradual weakening of the shear strength due to stress concentration during the coseismic slip of the mainshocks. Following the temporal decrease, the median Δ values then increase in the subsequent months, consistent with fault zone healing and an increase in fault strength (e.g., Goebel et al, 2015;Moyer et al, 2018;Vidale et al, 1994).…”
Section: Spatio-temporal Stress Drop Evolutionmentioning
confidence: 93%
“…A ratio of 1.27 corresponds to a rupture velocity of about 0.75 vs ${v}_{s}$, so we set k P as 0.33 and k S as 0.26 (Kaneko & Shearer, 2014) to compute the stress drops (4). Other studies have found similar vr/vs ${{v}_{r}/v}_{s}$ based on P / S corner frequency ratios in subduction zones (Yamada et al., 2021). Note however that this ratio is an average in space and time, and therefore the scattering can be explained by varying rupture velocities and geometries among events.…”
Section: Resultsmentioning
confidence: 62%
“…Some authors have found a degree of correlation between stress drops of microearthquakes and the coseismic slip areas of large earthquakes: stress drops were sometimes found to be high around past rupture zones and low within them (Yamada et al., 2021), although that correlation is ambiguous (Allmann & Shearer, 2007; Shearer et al., 2006). Similarly, Hardebeck and Aron (2009) found that stress drops of earthquakes in and around locked zones were higher on average than those on creeping portions of the Hayward fault (California) at similar depths, suggesting a link to coupling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the corner frequencies of the target earthquakes by applying the empirical Green's function (EGF) method following Yamada et al (2021), we selected nearby hypocenters from the hypocenter dataset of Nishimura et al ( 2023), which they relocated using the double-difference method (Waldhauser and Ellsworth 2000) and the JMA velocity structure model (Ueno et al 2002). They used the arrival-time differences for event pairs calculated from (i) JMA P-and S-wave arrivals as the catalog data and (ii) cross-spectra of velocity waveforms in the 1-8 Hz frequency band as the correlation data (Hayashi and Hiramatsu 2013).…”
Section: Methodsmentioning
confidence: 99%